A fresh look at the biodiversity lexicon for fiddler crabs (Decapoda: Brachyura: Ocypodidae). Part 1: Taxonomy. Issue 6 (8th November 2019) - Rosenberg, Michael S
Abstract: Fiddler crabs (Ocypodidae) have gone through a gradual series of taxonomic revisions and refinements over the last 40 years, culminating most recently with an expansion from a single genus into eleven different genera. I examine the opportunities presented by these revisions with respect to establishing formal names for previously established clades at a variety of taxonomic levels that were otherwise previously impossible to name due to historical compression of these crabs into a single genus, including the establishment or reestablishment of three tribes (Ucini, Gelasimini, and Minucini) and ten subgenera: Uca ( Uca ), Uca ( Acanthoplax ), Gelasimus ( Gelasimus ), Gelasimus ( Mesuca ), Austruca ( Austruca), Austruca ( Cuneatuca ), Austruca ( Sinduca ), Tubuca ( Tubuca ), Tubuca ( Australuca ), and Tubuca ( Angustuca ). A previously overlooked synonymy between Gelasimus excisa (Nobili, 1906 ) and G. neocultrimana (Bott, 1973 ) is discussed, and the former name is adopted as valid.